Pemilihan Moda Transportasi Buton Utara–Kendari Menggunakan Metode Simple Additive Weighting - La Ode Ashari Sani; Romy Suryaningrat Edwin; Nurrakhmad Arsyad (Jurnal Konstruksi, 2025)
This study analyzes transportation mode selection preferences on the strategic Buton Utara–Kendari route, which plays a vital role in inter-island connectivity. The research employs the Simple Additive Weighting (SAW) method for a quantitative descriptive analysis based on five service criteria: cost, travel time, convenience, comfort, and safety. Primary data were collected from 80 respondents distributed across four transportation modes: motorcycle, private car, Damri bus, and Wanci ship. The analysis results identify the private car as the most optimal transportation mode, with the highest preference score (V = 95.62). This superiority is primarily driven by excellent performance in comfort and safety criteria, both achieving perfect normalization scores (1.00). The findings confirm that service quality (benefit criteria) is the determining factor in decision-making, outweighing considerations of cost and time. Sensitivity testing reinforces the model’s validity, showing high stability—where the private car remains the top choice (V = 88.65) even under extreme parameter variations—while secondary modes display volatility when cost factors change. The study concludes that investment in improving service quality strategically shapes user preferences. The recommended policy implication is that the government should reorient transportation policies for archipelagic regions by developing integrated and adaptive services, emphasizing service quality improvement rather than merely focusing on cost efficiency.